2020
DOI: 10.1016/j.psj.2020.08.082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation of DL-methionine on tissue and plasma antioxidant status during heat-induced oxidative stress in broilers

Abstract: Exposure to high ambient temperature has been shown to impair growth performance and to cause oxidative stress in broilers. This study investigated the hypothesis that supplementation with methionine ( Met ) as DL-Met ( DLM ) more than the National Research Council recommendations improves growth performance and alleviates oxidative stress in broilers exposed to high ambient temperature. One-day-old male Cobb-500 broilers (n = 68) were allotted to 4 groups and phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 61 publications
(25 reference statements)
3
11
0
Order By: Relevance
“…We observed that supplementation of DLM led to a reduction of the concentrations of individual and total COPs in heat-processed thigh muscle. This finding agrees with a previous study which has shown that supplementation of DLM reduces the formation of COPs in heat-processed thigh muscle in broilers subjected to heat stress [15]. The inverse correlations between the concentration of GSH and vitamin C in thigh muscle and the concentrations of COPs in heat-processed thigh muscle indicates that the reduced formation of COPs was due to increased concentrations of those antioxidants in the muscle.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We observed that supplementation of DLM led to a reduction of the concentrations of individual and total COPs in heat-processed thigh muscle. This finding agrees with a previous study which has shown that supplementation of DLM reduces the formation of COPs in heat-processed thigh muscle in broilers subjected to heat stress [15]. The inverse correlations between the concentration of GSH and vitamin C in thigh muscle and the concentrations of COPs in heat-processed thigh muscle indicates that the reduced formation of COPs was due to increased concentrations of those antioxidants in the muscle.…”
Section: Discussionsupporting
confidence: 92%
“…They contained nipple drinkers and automated feeders allowing the birds free access to feed and water. Light intensity and the light:dark regime were in accordance with our recent study [15]. The room temperature decreased from 29.5 • C on day 1, measured at pen height, to 21.0 • C on day 35.…”
Section: Animals Husbandry Diets and Experimental Designsupporting
confidence: 91%
See 3 more Smart Citations